Linkages Amongst Corporate Non-Compliance, Corruption & Corporate Crimes (in India) - Kulkarni, Arun (Digital Repository of Theses - SSBM Geneva, 2023)
The Indian economy has been growing rapidly over the past two decades, making it the world‘s fastest-growing economy and the second most populous country. With a growing and educated middle class and a strong rule of law, India offers many opportunities for global corporations. However, corruption has been a systemic issue in Indian business, despite significant efforts by international organisations and the Indian government to combat it. Transparency International reports reveal the extent of corruption in both developed and developing nations. Greed and unethical practices are commonplace as organizations seek to avoid onerous tasks and costly compliance requirements. Non-adherence to corporate governance is rising, making it difficult for preventive legislation to succeed. To do business in India, it‘s essential to understand the country‘s risks and compliance requirements. This study aims to explore the primary linkage between non- compliance and corruption in India and to investigate the factors that establish linkages between corruption, non-compliance, and corporate crime. The study includes an online survey of 70 compliance professionals from different industry segments and face-to-face interviews with 11 business leaders. The survey and interviews reveal several practical key points and lead us to conclude and recommend that- I. Compliance regimes should be simplified and decriminalised to prevent entities from engaging in unethical practices to avoid severe punishments. II. Regulators must proactively monitor non-compliances. III. Corporate entities should focus on ethical business practices, and all stakeholders should be oriented towards it through training and awareness programs. IV. Digitization should take priority in all compliances to minimize human interface with authorities. In conclusion, both the government and business communities must adopt practices that promote ethical business conduct to control and minimise corruption.